2012
DOI: 10.4161/psb.20468
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cell wall composition related to stem lodging resistance in wheat (Triticum aestivumL.) by FTIR spectroscopy

Abstract: We explored the rapid qualitative analysis of wheat cultivars with good lodging resistances by Fourier transform infrared resonance (FTIR) spectroscopy and multivariate statistical analysis. FTIR imaging showing that wheat stem cell walls were mainly composed of cellulose, pectin, protein, and lignin. Principal components analysis (PCA) was used to eliminate multicollinearity among multiple peak absorptions. PCA revealed the developmental internodes of wheat stems could be distributed from low to high along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Plant cell walls are complex composites of cellulose, cross-linking glucans, protein, and pectin substances. This technique can be applied to analyze stems of wheat cultivars via the spectral fingerprinting of cell walls and to identify chemical differences between genotypes with varying levels of lodging resistance (Wetzel & LeVine 2000;Wang et al 2012). From our results, we found that the shifts in the absorbance intensities at different frequencies between control and treated leaves can be related to the concentrations of different molecules such as cellulose, protein, pectin, and lignin.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Plant cell walls are complex composites of cellulose, cross-linking glucans, protein, and pectin substances. This technique can be applied to analyze stems of wheat cultivars via the spectral fingerprinting of cell walls and to identify chemical differences between genotypes with varying levels of lodging resistance (Wetzel & LeVine 2000;Wang et al 2012). From our results, we found that the shifts in the absorbance intensities at different frequencies between control and treated leaves can be related to the concentrations of different molecules such as cellulose, protein, pectin, and lignin.…”
Section: Resultsmentioning
confidence: 61%
“…Apparently, the β-sheet secondary structure of protein, indicated by an amide I band maximum centered at 1621 cm −1 is more intense in the control group compared with treated cassava. In contrast, the absorbance in the polysaccharide region (1200-900 cm −1 ) is shown to be higher in the treated plant (Séné et al 1994;Wang et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In common wheat, traits that are most correlated with lodging resistance are: plant height, stem length, stem diameter, stem and spike weight, stem wall thickness, and mechanical layer thickness (Kelbert et al, 2004a,b;Kong et al, 2013;Wang et al, 2006;Zuber et al, 1999). Recent studies investigated the correlations between lodging resistance and the concentrations of cellulose, lignin, pectin, and protein in the stem (Kong et al, 2013;Wang et al, 2012). Strong correlations between plant height and lodging resistance were noted in modern cultivars of common wheat by Kelbert et al (2004a,b), who studied the effects of artificially induced lodging on 13 and 25 genotypes of spring wheat, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific advancements contributed to the development of a diagnostic method based on Fourier transform infrared resonance (FTIR) and principal component analysis (PCA). This method is used to evaluate variations in the chemical composition of cell walls that determine the mechanical properties of stems (Wang et al, 2012). The correlations between various plant traits and lodging resistance have been widely studied, but an index of resistance traits that could be used in breeding programs has not yet been developed.…”
Section: Introductionmentioning
confidence: 99%